The values of pancasila and the 1945 constitution in the actualization products of the basic training program for civil servant candidates at the ministry of religious affairs: realizing impactful BerAKHLAK civil servants - Septri Rahayu; Riana Antika Amahoroe; Rahmadani (Balai Diklat Keagamaan Ambon, 2026)
This study examines the implementation of Pancasila values and the 1945 Constitution of the Republic of Indonesia within the Basic Training Program for Civil Servant Candidates (LATSAR CPNS) of the Ministry of Religious Affairs through state-defense action plans and participants’ actualization projects. Employing a qualitative case study approach, the research involved 68 Grade III civil servant candidates in Maluku and North Maluku Provinces. Data were collected through document analysis of actualization reports, interviews, observations, and supporting training documents. The findings reveal that the implementation of Pancasila and constitutional values was manifested through five forms of state-defense action plans: strengthening operational discipline, promoting national insight and religious moderation, fostering administrative integrity, implementing pro-social service initiatives, and developing collaborative initiatives. The innovation products generated by participants were categorized into five groups: digital learning media, digital systems and applications, standard operating procedure (SOP) guidebooks and booklets, administrative service models, and community-based programs. The analysis indicates that Pancasila and constitutional values function not merely as normative principles but also as practical references that guide the development of innovations aimed at improving service quality, strengthening organizational governance, and addressing workplace challenges. The impacts of these innovations were reflected in enhanced institutional efficiency, improved accessibility and quality of public services, and increased public awareness of national values and religious moderation. This study demonstrates that LATSAR CPNS serves as an effective mechanism for translating national and constitutional values into contextual innovation practices, thereby contributing to the development of professional, integrity-driven, and service-oriented civil servants.